Teachers’ Emotional Exhaustion Scale (TEES): Development and Psychometric Validation - Jonathan Martínez-Líbano (Education Sciences)
Emotional exhaustion in schoolteachers is a critical issue due to its detrimental effects on teachers’ mental health and its potential negative impact on students’ academic outcomes. This study aimed to develop and validate the Teachers’ Emotional Exhaustion Scale (TEES). The research was conducted in three phases. First, the scale items were developed and evaluated by expert judges using Aiken’s V for content validation. Second, an exploratory factor analysis (EFA) was performed on a sample of 153 teachers to identify the scale’s factor structure. Finally, a confirmatory factor analysis (CFA) was conducted with a sample of 473 Chilean teachers to validate the factor structure. The EFA revealed a two-factor structure comprising Emotional Fatigue (EF) and Emotional Hopelessness (EH), which was subsequently confirmed in the CFA. The model demonstrated a satisfactory fit to the data: χ2(32) = 142.383, p < 0.001; CMIN/DF = 1.651. The goodness-of-fit indices were robust (GFI = 0.933, NFI = 0.952, IFI = 0.981, TLI = 0.974, CFI = 0.980), and the RMSEA was 0.065, indicating an acceptable model fit. The TEES is a valid and reliable instrument for assessing emotional exhaustion in teachers. These findings are particularly relevant in the Chilean educational context, where teachers’ mental health and its implications for the education system are of increasing concern. The TEES can serve as a valuable tool for the early identification of emotional exhaustion, ultimately contributing to teacher retention and the improvement of educational quality.